Contents: Macromol. Chem. Phys. 13/2016. Issue 13 (4th July 2016) - Jaksch, Sebastian; Schulz, Anita; Di, Zhenyu; Luxenhofer, Robert; Jordan, Rainer; Papadakis, Christine M.
Abstract : Back Cover : Amphiphilic triblock copolymers from poly(2‐oxazoline)s solubilize huge amounts of the strongly hydrophobic cancer drug paclitaxel. Small‐angle neutron scattering revealed a possible reason: Paclitaxel forms small domains which are not only located within the micellar core but also at the interface between the core and the shell of the micelle. Further details can be found in the article by Sebastian Jaksch, Anita Schulz, Zhenyu Di, Robert Luxenhofer, Rainer Jordan, and Christine M. Papadakis* on page 1448.